Fresh Submarine Groundwater Discharge Augments Growth in a Reef Fish - Lilkendey, Julian; Pisternick, Timo; Neumann, Sarah I.; Dumur Neelayya, Danishta; Bröhl, Stefanie; Neehaul, Yashvin; Moosdorf, Nils (Frontiers in Marine Science, 2019)
Fresh submarine groundwater discharge (fresh SGD), the efflux of terrestrial groundwater directly into the ocean, is a ubiquitous pathway for nutrient-rich freshwater to coastal ecosystems, altering their hydrography, hydrochemistry, and primary productivity. Yet only little is known about the effects of fresh SGD on the fitness of higher trophic levels such as teleost fish. Otolith analysis revealed that somatic growth rates were significantly higher and settlement to reef habitat took place significantly earlier in juvenile grey demoiselle Chrysiptera glauca exposed to fresh SGD as compared to strictly marine conditions. Contrary to expectations, feeding conditions were comparable in both habitats. We propose that physiologically beneficial environmental conditions brought about by the submarine influx of cold acidic freshwater enabled juvenile fish to exhibit elevated growth rates, thereby increasing their survival potential. This effect would directly link changes in groundwater on land to variations in marine primary and secondary consumer biomass at the coast.